2013
DOI: 10.4236/ijcm.2013.411088
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Emergency Codes in Hospitals

Abstract: Background: Hospitals must be prepared to deal efficiently and effectively with different emergencies. To accomplish this, several countries have standardized their hospital emergency codes to improve their response capability. This is particularly important in Puerto Rico given that many health professionals, particularly physicians and nurses, provide services in more than one hospital. This study examined the emergency codes and alerts utilized in Puerto Rican hospitals. Objective: To assess hospitals' leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Surveys of hospital emergency codes in California, Florida, and Puerto Rico have confirmed that there is significant variety among different hospital emergency code systems. [1][2][3] These surveys found some limited agreement across the color code systems of different states; however, different health care systems and jurisdictions frequently use codes that are unique to their limited geographic area. As of May 2018, at least 12 different state hospital associations, patient safety organizations, and health care worker organizations have recommended the use of plain language in hospitals (Colorado, 4 Emergency Nurses Association, 5 Florida, 2 Iowa, 6 Minnesota, 7 Missouri, 8 North Carolina, 9 Pennsylvania, 10 South Carolina, 11 Texas, 12 and Wisconsin 13 ).…”
Section: B Ac K G Ro U N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys of hospital emergency codes in California, Florida, and Puerto Rico have confirmed that there is significant variety among different hospital emergency code systems. [1][2][3] These surveys found some limited agreement across the color code systems of different states; however, different health care systems and jurisdictions frequently use codes that are unique to their limited geographic area. As of May 2018, at least 12 different state hospital associations, patient safety organizations, and health care worker organizations have recommended the use of plain language in hospitals (Colorado, 4 Emergency Nurses Association, 5 Florida, 2 Iowa, 6 Minnesota, 7 Missouri, 8 North Carolina, 9 Pennsylvania, 10 South Carolina, 11 Texas, 12 and Wisconsin 13 ).…”
Section: B Ac K G Ro U N Dmentioning
confidence: 99%
“…Surveys of hospital emergency codes in California, Florida, and Puerto Rico have confirmed that there is significant variety among different hospital emergency code systems . These surveys found some limited agreement across the color code systems of different states; however, different health care systems and jurisdictions frequently use codes that are unique to their limited geographic area.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has to be a government priority to identify communities exposed to different natural and physical hazards, to characterize their vulnerability, evaluate shelters capacity (temporary and emergency) and evaluate the State Emergency Response and Recovery Plan. In case of an emergency, temporary and emergency shelters must be able to provide daily necessities such as food, water, sleeping arrangement, and other needed services [16] However government dependencies tend to have limited capability to respond to disasters, specifically when homes and settlements are fully destroyed or severely damaged [17]. Another important complex element of community recovery is associated with the infrastructure that is fundamental for the operations of other systems dependent upon transportation, electricity, water, and waste disposal to carry out their normal activities [16].…”
Section: Journal Of Geology and Geosciencesmentioning
confidence: 99%
“…BLS procedure includes cardiopulmonary resuscitation in (CPR), bleeding control, artificial ventilation and basic airway management. [15][16][17] BLS and ACLS training has been routinely recommended training procedure for all healthcare professionals. However, these trainings are not routinely practice in developing countries like India.…”
Section: Introductionmentioning
confidence: 99%